A new species of Noccaea (Brassicaceae) from central Anatolia - Özgi̇şi̇ Kurtuluş (Phytotaxa, 2020)
Noccaea atila-ocakii is described as a new species from Eskisehir, Turkey. Morphologically, it is similar to N. antitaurica and N. lilacina, but it is easily distinguished by several morphological characters, including the size of its basal leaves, shape of its cauline leaves and fruit, length of its style, number of ovules, etc. Phylogenetic relationships, based on the nuclear-encoded ribosomal internal transcribed spacer (ITS) region, within the genus are shown. Molecular data reveal that new species clearly differs from N. antitaurica and N. lilacina. Paraphyletic taxa in the phylogenetic tree also indicate that the generic circumscription of Noccaea by Al-Shehbaz is more convenient compared with previous delimitations of this genus. Diagnostic characters, a detailed description, and photographs of the new species are given; the IUCN Red List category and observations on the ecology of the populations are noted; and the distribution map of the new species and its closely related species in Turkey are presented.